(E)-Ethyl 2-cyano-3-(furan-2-yl)acrylate - Kalkhambkar, Rajesh G. (International Union of Crystallography, 2012)
There are two independent molecules in the asymmetric unit of the title compound, C(10)H(9)NO(3), in both of which, all non-H atoms except for the methyl C atom lie nearly in the same plane [maximum deviations = 0.094 (3) and 0.043 (2) Å]. In the crystal, each independent molecules is linked by pairs of C—H⋯O interactions, generating inversion dimers with R (2) (2)(10) ring motifs.